(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Breast cancer is a heterogeneous disease, the pathogenesis of which is determined by the complex interaction of hormonal, metabolic, exogenous and other factors and is the most common malignant neoplasm among women in the world. According to various authors, breast cancer is characterized as a tumor that often metastasizes to the bones (from 13.5 to 85%), and in terms of the frequency of localization of metastatic lesions, the skeleton ranks third after the lungs and liver. Metastatic bone damage in breast cancer is an urgent problem. Most patients are indicated for osteomodifying therapy. The article defines a portrait of a patient for whom the use of antiresorptive drugs can be postponed or canceled. The results of the registration study showed that denosumab is not only not inferior in effectiveness to zoledronic acid, but also reduces the risk of development and significantly delays the onset of the first and subsequent skeletal complications, including the need for radiation therapy, the development of hypercalcemia and pathological fractures. Denosumab is an effective, well-tolerated drug that increases the chance of preventing RCM in breast cancer.